THE IMPACT OF SOCIAL MEDIA ON STUDENT ACADEMIC PERFORMANCE AND WELL-BEING - Faiza Maham Faizee; Sehar Anees; Prof. Dr. Muhammad Ismail Kumbhar; Dr. Aamir Riaz; Muhammad Hamid Nawaz Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
Social media platforms are experiencing fast growth among the younger population worldwide. Students extensively participate in the use of social media. Consequently, they will have an impact on both the personal and academic lives of students. This study aims to determine the influence of social media on the academic performance and well-being of students. The survey method was utilized to gather the relevant information for the investigation. A total of 324 students were chosen as the sample. A random sampling strategy was utilised to choose the sample. Afterwards, the data was analyzed using Statistical Technique. The findings indicated that the majority of students in the society expressed a preference for utilising social media in a constructive manner for their academic pursuits, rather than engaging in its misuse. This suggests that social media has an influence on the academic achievement of kids. Hence, social media plays a role in enhancing kids' academic achievement. Nevertheless, the findings indicated notable disparities in academic achievement and the influence of social media on students' well-being. Instructor Social media can be utilised by students as well as teachers as a tool for teaching and learning, with the aim of facilitating and enhancing the learning process. Evidence from research indicates that a significant proportion of pupils are experiencing addiction to social media. In order to achieve this objective, the researcher proposed that social media should also be utilised for educational purposes. It was suggested that Social Networking Sites should be expanded and new pages should be established to improve academic activities and prevent any negative impact on students' academic performance. Additionally, it was recommended that teachers and parents should closely supervise students' usage of these sites. The purpose of this initiative is to establish equilibrium between students' engagement with social media and their academic pursuits, in order to prevent any negative impact on their academic performance and overall well-being.